Tumor suppressive microRNA-124a inhibits stemness and enhances gefitinib sensitivity of non-small cell lung cancer cells by targeting ubiquitin-specific protease 14. (28th July 2018) - Yu, Fei; Liu, Ji-Bin; Wu, Zhi-Jun; Xie, Wen-Ting; Zhong, Xiao-Jun; Hou, Li-Kun; Wu, Wei; Lu, Hai-Min; Jiang, Xiao-Hui; Jiang, Jun-Jian; Cao, Zi-Yang; Cong, Gu-Jun; et al.
Abstract: Increasing evidence has shown that microRNAs (miRNAs) play a significant functional role by directly regulating respective targets in cancer stem cell (CSC)-induced non-small cell lung cancer (NSCLC) progression and resistance to therapy. In this study, we found that hsa-miR-124a was downregulated during spheroid formation of the NSCLC cell lines SPC-A1 and NCI-H1650 and NSCLC tissues compared with normal lung cells and tissues. Patients with lower hsa-miR-124a expression had shorter overall survival (OS) and progression free survival (PFS). Moreover, ubiquitin-specific protease 14 (USP14) was confirmed to be a direct target of hsa-miR-124a. Furthermore, concomitant low hsa-miR-124a expression and high USP14 expression were correlated with a shorter median OS and PFS in NSCLC patients. Cellular functional analysis verified that the tumor suppressor hsa-miR-124a negatively regulated cell growth and self-renewal, and promoted apoptosis and gefitinib sensitivity of lung cancer stem cells by suppressing its target gene USP14. Our results provide the first evidence that USP14 is a direct target of hsa-miR-124a, and that hsa-miR-124a inhibits stemness and enhances the gefitinib sensitivity of NSCLC cells by targeting USP14. Thus, hsa-miR-124a and USP14 may be useful as tumor biomarkers for the diagnosis and treatment of NSCLC. Highlights: Hsa-miR-124a regulates growth, self-renewal and gefitinib sensitivity of LCSCs by suppressing USP14. USP14 is a direct target of hsa-miR-124a. NSCLC patients with high USP14 expression and low hsa-miR-124a expression had significantly decreased OS and PFS. Hsa-miR-124a and USP14 may be useful as tumor biomarkers for the diagnosis and treatment of NSCLC.